Child maltreatment research, policy and practice for the next decade: workshop summary - Olson, Steve (National Academies Press)
Introduction and overview -- Reflections on the 1993 NRC report, Understanding child abuse and neglect -- Recognizing and assessing child maltreatment -- Social trends and child maltreatment trends -- Causes and consequences of child maltreatment -- Preventing child maltreatment -- Design and delivery of services -- Systems-level issues -- Closing remarks and research opportunities